Child with liver transplant recovers from COVID-19 infection. A case report - Morand, Aurélie (Arch Pediatr, 2020)
We present the case of a 55-month-old girl who recovered from coronavirus disease 2019 (COVID-19) infection 5 months after undergoing liver transplantation; she had a co-infection with Epstein–Barr virus (EBV). To the best of our knowledge, this is the first case report of a COVID-19 infection in a pediatric patient with liver transplantation. Additionally, this is also the first report of confirmed co-infection between COVID-19 and EBV. On the basis of this case, we suggest that liver transplantation is not associated with COVID-19 symptom severity and development. Moreover, COVID-19 and EBV co-infections do not seem to aggravate the clinical outcome.